SFDI biomarkers provide a quantitative ulcer risk metric and can be used to predict diabetic foot ulcer onset - Lee, Suzette; Mey, Leann; Szymanska, Agnieszka F.; Takhar, Harpreet S.; Cuccia, David J.; Mazhar, Amaan; Yu, Kalvin (Journal of diabetes and its complications, 2020)
Annually, up to 4% of people with diabetes present with a chronic foot ulcer. Quantitative real-time testing to identify patients at risk for ulceration can guide preventative care. Here, we assess whether a non-invasive optical imaging technique, Spatial Frequency Domain Imaging (SFDI), can identify patients at the highest risk for ulceration and predict ulcer onset. We imaged 252 subjects with diabetes at Kaiser Permanente, Southern California. SFDI derived tissue biomarkers of microcirculation were compared between subjects with and without a history of ulceration, and subjects who did or did not develop ulcers after 1 year. Feet of subjects at the highest risk (i.e. history of ulceration) had significantly lower hemoglobin in the papillary dermis (HbT1), along with higher oxygenation (StO2) due to poor extraction. These subjects also had more homogeneous hemoglobin spread in the reticular dermis (HbT2) and tissue scattering (related to skin structure). Prediction based on HbT1 and tissue scattering identified new ulcerations and performed with sensitivity/specificity of 68.8%/64.8% and 75.0%/69.1%, respectively. These results show that SFDI hemoglobin distribution and oxygenation biomarkers provide a quantitative basis for ulcer risk stratification and ulcer onset prediction. •Annually, up to 4% of people with diabetes present with a chronic foot ulcer.•Quantitative real-time testing to identify patients at risk for ulceration can guide preventative care.•Spatial Frequency Domain Imaging (SFDI) is a non-invasive optical imaging technique that can assess microcirculation in tissue.•SFDI derived microcirculation biomarkers could identify patients at the highest risk for ulceration and predict ulcer onset.